Directly converted patient-specific induced neurons mirror the neuropathology of FUS with disrupted nuclear localization in amyotrophic lateral sclerosis. Issue 1 (December 2016) - Lim, Su; Choi, Won; Oh, Ki-Wook; Xue, Yuanchao; Choi, Ji; Kim, Sung; Nahm, Minyeop; Kim, Young-Eun; Lee, Jinhyuk; Noh, Min-Young; Lee, Seungbok; Hwang, Sejin; et al.
Abstract Background Mutations in the fused in sarcoma (FUS ) gene have been linked to amyotrophic lateral sclerosis (ALS). ALS patients withFUS mutations exhibit neuronal cytoplasmic mislocalization of the mutant FUS protein. ALS patients' fibroblasts or induced pluripotent stem cell (iPSC)-derived neurons have been developed as models for understanding ALS-associated FUS (ALS-FUS) pathology; however, pathological neuronal signatures are not sufficiently present in the fibroblasts of patients, whereas the generation of iPSC-derived neurons from ALS patients requires relatively intricate procedures. Results Here, we report the generation of disease-specific induced neurons (iNeurons) from the fibroblasts of patients who carry three differentFUS mutations that were recently identified by direct sequencing and multi-gene panel analysis. The mutations are located at the C-terminal nuclear localization signal (NLS) region of the protein (p.G504Wfs*12, p.R495*, p.Q519E): twode novo mutations in sporadic ALS and one in familial ALS case. Aberrant cytoplasmic mislocalization with nuclear clearance was detected in all patient-derived iNeurons, and oxidative stress further induced the accumulation of cytoplasmic FUS in cytoplasmic granules, thereby recapitulating neuronal pathological features identified in mutant FUS (p.G504Wfs*12)-autopsied ALS patient. Importantly, such FUS pathological hallmarks of the patient with the p.Q519E mutation were only detected in patient-derived iNeurons, which contrasts to predominant FUS (p.Q519E) in the nucleus of both the transfected cells and patient-derived fibroblasts. Conclusions Thus, iNeurons may provide a more reliable model for investigating FUS mutations with disrupted NLS for understanding FUS-associated proteinopathies in ALS.